(untitled) (Journal of Comparative & International Higher Education, 2022)
In Canada, research has examined international-local student interaction by focusing on international students’ perceptions and experiences. As such, the perspectives of local students toward socialization with international students remain less explored. Designed as a survey-based case study with 17 local students at a university in Ontario, this study sought to understand the perspectives of local students on how to improve socialization between the two groups. Additionally, this study investigated how local students conceptualized their experiences of multiculturalism and multilingualism at their university, considering the importance of diversity for the development of intercultural knowledge and intercultural relationships. Findings suggest that local students considered their university to be multicultural/multilingual primarily based on the availability of cultural events and different languages being spoken on campus. Additionally, local students ascribed much importance to socialization with international students, but expected the university to assume a more formal role in developing structured opportunities for the two groups to come together.